2015
DOI: 10.1007/s13277-015-3495-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of osteopontin expression in melanoma progression

Abstract: It was shown that osteopontin (OPN), a glycophosphoprotein, plays divergent roles in cancer progression. In addition to multiple intra-and extracellular functions, it facilitates migration of tumor cells, has crucial role in cell adhesion and is associated with increased metastasis formation. In previous studies, we performed global gene-expression profiling on a series of primary melanoma samples and found that OPN was significantly overexpressed in ulcerated melanomas. The major purpose of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…A study on patients with pancreatic ductal adenocarcinoma (PDAC) demonstrated that serum levels of OPN are elevated with advanced tumour grades (44). Elevated OPN levels have also been strongly associated with increased stage, grade and tumour size in melanoma patients (52). In early stage non-small cell lung cancer (NSCLC) patients high OPN plasma levels were observed which were reduced after surgical tumour resection.…”
Section: Expression Of Opn In Human Cancermentioning
confidence: 99%
“…A study on patients with pancreatic ductal adenocarcinoma (PDAC) demonstrated that serum levels of OPN are elevated with advanced tumour grades (44). Elevated OPN levels have also been strongly associated with increased stage, grade and tumour size in melanoma patients (52). In early stage non-small cell lung cancer (NSCLC) patients high OPN plasma levels were observed which were reduced after surgical tumour resection.…”
Section: Expression Of Opn In Human Cancermentioning
confidence: 99%
“…This was due to the lack of osteopontin cleavage in the MT4-MMP -/-mice [7]. Osteopontin is a glycoprotein in the ECM with versatile functions in tumor progression, including the enhancement of tumor cell migration [33][34][35]. Hence, increased MT4-MMP activity could result in increased migratory potential in tumors due to osteopontin cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, increased osteopontin correlates with increased metastasis and often poor survival in multiple types of cancer including laryngeal squamous cell carcinoma (Chen et al 2015), melanoma (Kiss et al 2015), nasopharyngeal carcinoma (Hou et al 2015) and breast cancer (Xu et al 2015). Lenga et al (2008) reported that osteopontin was required for TGFβ1 transdifferentiation of cardiac fibroblasts to myofibroblasts, whereas Weber et al (2015) provided evidence that osteopontin induced bone-marrow-derived mesenchymal suppressor cells to become myofibroblasts.…”
Section: Tgfβ1-driven Changes In the Tumour Microenvironment Can Prommentioning
confidence: 99%